التواصل التربوي من السلامة اللغوية المفقودة إلى النجاعة التبليغية المنشودة - صابري، بوبكر الصديق (جامعة محمد البشير الإبراهيمي برج بوعريريج - كلية الآداب واللغات, 2016)
Person concerned in the field of teaching –languages notices the details of the process that is underlined by the development of teaching – methods. There is no doubt, he will conclude that structuralist methods emphasize more on the linguistic correctness which use different teaching means to achieve a goal, that the fact prove its sterility in the linguistic creativity, because teaching operation is based on the learning and not on the acquisition. Indeed, educational communication can not be only linguistic correctness, but it is also the acting, the making and the creativity. This goal can be realized if we take on consideration the linguistic correctness which is the step of learning as well as the effectiveness of transmission.
يدرك المهتم بحقل تعليمية اللغات تفاصيل المسار الذي رسمه تطور طرائق التعليم في هذا الحقل، وقد يخلص ولا شك أن الطرائق البنيوية ركزت أكثر على السلامة اللغوية فاستنفرت لذلك وسائل تعليمية لبلوغ هدف أثبت الواقع عقمه في الإبداع اللغوي، لا لشيء إلا لأنه يقوم على التعلم لا على الاكتساب. ولما كان التواصل التربوي في حقيقته ليس سلامة لغوية فحسب كان لزاما الاهتمام بالتواصل التربوي في بعده الإنجازي، ولا يمكن تحقيق ذلك بالتوقف عند السلامة اللغوية وعدم بلوغ النجاعة التبليغية.
Keywords: اللسانيات -- تعليم اللغات -- التواصل التربوي -- السلامة اللغوية